Circadian rhythms revealed: unraveling the genetic, physiological, and behavioral tapestry of the human biological clock and rhythms - Morin, Renée; Forest, Geneviève; Imbeault, Pascal (Frontiers in Sleep, 2025)
This narrative review explores the intricate relationship between biological rhythms and the natural cycles of light and darkness, known as circadian rhythms. This review begins with an examination of empirical evidence dating back to 1729, which indicates that a particular plant displayed rhythmic behavior even in complete darkness. It then considers the evolution and significance of internal biological clocks in humans. The pivotal role of circadian rhythms in regulating physiological processes (e.g., sleep-wake cycles, body temperature, and hormone levels) emphasizing their influence on overall health and wellbeing is discussed. This review also highlights the critical importance of maintaining circadian timing alignment with the environment, as desynchronization can lead to a range of adverse outcomes, including cardiovascular, metabolic, and psychological disorders. By integrating the genetic, physiological, and behavioral mechanisms underlying and associated with biological clocks and rhythms in humans, this review aims to provide clinicians and researchers with a comprehensive perspective on the holistic nature of biological rhythms and their implications for health. Furthermore, the concepts associated with Chrono-intervention, such as chrononutrition and chronomedicine, are introduced as promising approaches to optimizing health outcomes by aligning interventions with the body's natural rhythms are introduced. Through this consideration, this review seeks to contribute to a deeper understanding of chronobiology and its potential applications in improving human health and performance.